2019
DOI: 10.1038/s41598-019-45966-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cathepsin S Reduces Lacrimal Gland Inflammation and Increases Tear Flow in a Mouse Model of Sjögren’s Syndrome

Abstract: Cathepsin S (CTSS) is highly increased in Sjögren’s syndrome (SS) patients tears and in tears and lacrimal glands (LG) of male non-obese diabetic (NOD) mice, a murine model of SS. To explore CTSS’s utility as a therapeutic target for mitigating ocular manifestations of SS in sites where CTSS is increased in disease, the tears and the LG (systemically), the peptide-based inhibitor, Z-FL-COCHO (Z-FL), was administered to 14–15 week male NOD mice. Systemic intraperitoneal (i.p.) injection for 2 weeks significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 63 publications
1
18
1
Order By: Relevance
“…Recently, CTSS activity was observed to be elevated in Sjögren's syndrome patient tears, which results in tear protein degradation [83]. Systemic or topical administration of a CTSS inhibitor reduced symptoms in a mouse model of Sjögren's syndrome [84]. Therefore, CTSS appears to play a role in autoimmune responses and represents a potential therapeutic target to treat these diseases in addition to the pulmonary diseases already outlined in this review.…”
Section: Autoimmune Diseasesmentioning
confidence: 81%
“…Recently, CTSS activity was observed to be elevated in Sjögren's syndrome patient tears, which results in tear protein degradation [83]. Systemic or topical administration of a CTSS inhibitor reduced symptoms in a mouse model of Sjögren's syndrome [84]. Therefore, CTSS appears to play a role in autoimmune responses and represents a potential therapeutic target to treat these diseases in addition to the pulmonary diseases already outlined in this review.…”
Section: Autoimmune Diseasesmentioning
confidence: 81%
“…Recently, inhibition of Cathepsin S with a peptide-based inhibitor was shown to reduce inflammation in lacrimal glands and mitigate ocular manifestations of Sjogren's syndrome, reducing the abundance of CD68positive lymphocytes. 61 The expression of cathepsin S is also induced in response to injury and inflammation in muscles where it participates in remodeling the extracellular matrix, while its deletion minimized the pathological changes in the tissues. 62 Thus, downregulation of its gene Ctss could be interpreted as an evidence of a functional link between Elovl3 and Ctss and a physiological response in an attempt to reduce inflammation in the tissues of E3hom mice.…”
Section: Impact Of Elovl3 Inactivation On Mg Transcriptomementioning
confidence: 99%
“…This study is the first to link Rab27a directly to CTSS secretion in the LG. Our finding is of potential clinical relevance since CTSS is implicated in the etiology of SS [ 29 ]. Continuing functional studies and evaluation of protein trafficking in disease-model and healthy mice may in future provide new targets for therapeutic therapeutic development.…”
Section: Discussionmentioning
confidence: 82%
“…Elevated CTSS in tears and LG may disrupt surface homeostasis and reinforce lymphocyte recruitment [ 18 ]. In vitro studies have shown that CTSS, at concentrations equal to those found in SS patient tears, induces release of pro-inflammatory cytokines from cultured corneal epithelial cells [ 29 ]. CTSS is also involved in activation and release of the chemokine, CX3CL1, from LG acinar cells (LGAC) and into tears in male NOD mice [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation